Splash [videorecording (DVD)] - Howard, Ron, 1954-; Hanks, Tom; Hannah, Daryl; Levy, Eugene, 1946-; Candy, John (Buena Vista Home Entertainment, 2004)
The story of a workaholic who thinks he will never find love and the mermaid who comes ashore to find him and prove him wrong.